Kajian Manuk Dewata pada Hiasan Kerajinan Bungkung Bali “Ornamen Bali” - I Putu Sinar Wijaya; Ngurah Adhi Santosa (Journal on Education, 2022)
Balinese jewelery from the royal era is still popular and has also been developed by several jewelery craftsmen, with existing and new designs and motifs, Balinese handicrafts with manuk dewata motifs and the addition of Balinese ornaments, where the manuk dewata motif has a different philosophy. Strong with Balinese Hindu culture and customs. The method used is descriptive research which aims to describe, record, analyze and interpret current conditions that occur in the field. Types and approaches are very important in the preparation of research, while the type of research used is qualitative research. Manuk Dewata itself, especially in Bali, is used as a symbol in the Ngaben ceremony because it is believed to be a spirit that conveys immortality, so Balinese craftsmen make humung jewelry designs with manuk dewata motifs with a combination of other Balinese ornaments, thus creating a work of jewelry made of bamboo made of gold and gold. silver, from the royal era until now is called and known by the manuk dewata motif. The manuk dewata motif was requested because this motif looks classic and timeless, it even looks more dignified for those who wear jewelry with this manuk dewata motif.